Reasonableness of restrictions on freedom of expression in Pakistan - Fatiana, Yasir Aleem; Abdul Wahab, Harlida; Halim, Rohizan (International Science Community Association, 2018)
Freedom of Expression like all other fundamental rights is not absolute in Pakistan. Restrictions can be imposed by the state according to the procedure established by the law. However constitution of Pakistan has added a condition of “Reasonableness” for restrictions on Freedom of expression. This article focuses on the test to decide "Reasonableness" of restrictions imposed upon freedom of expression. This article also explores principles embraced by the superior courts for determination of “Reasonableness” of restrictions. The later portion of this article highlights the restrictions enforced on freedom of expression in Pakistan